PERANAN PENYULUH AGAMA DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN BAGI MASYARAKAT KECAMATAN TANETE RIATTANG TIMUR KABUPATEN BONE - Musliamin Musliamin (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2019)
This study discusses "The Role of Religion in Improving UnderstandingReligious For Communities in Tanete Riattang Timur District, Bone Regency.The purpose of this study is to perfect the pictureto increase understanding of religion forcommunity. This research uses the field research method vizthe method used by conducting research on the object of studywith interview, observation and documentation methods. Is a source of data inthis research is the religious extension staffs of Tanete Riattang Timur DistrictBone Regency. Data that has been collected from the results of research conducted withusing qualitative descriptive analysis techniques. The results showed that,1) The role of the KUA religious instructor in Tanete Riattang Timur District, Bone Regencyin increasing religious understanding for the community by means of meanseducate, rectify, elaborate and unite in providing understandingreligious. 2) The method used by KUA religious instructors in Tanete DistrictRiattang Timur Bone Regency in improving religious understanding withdirect communication methods, individuals, groups and communication are notImmediately provide religious understanding for the community. 3) ExtensionKUA religion Tanete Riattang Timur District Bone in improvingReligious understanding for the community is by providing understandingreligion Regarding the Aqeedah, Sharia, and Morals